PENGARUH VARIASI KONSENTRASI TRIETHANOLAMINE TERHADAP STABILITAS FISIK LOTION EKSTRAK DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) - Yulia Rika Femina; Gigih Kenanga Sari; Maulita Saraswati (Joseph: Journal of Science and Pharmacy, 2025)
Background: Fragrant pandan leaves (Pandanus amaryllifolius Roxb.) are known to contain various secondary metabolites such as alkaloids, flavonoids, tannins, saponins, and terpenoids, making them potentially useful as ingredients in herbal cosmetic formulations, especially lotions. Triethanolamine acts as an emulsion stabilizer for oil-in-water (O/W) emulsions. Variations in triethanolamine concentration are expected to affect the physical stability of the lotion, thus further research is needed to optimize the formulation. Purpose: This study aims to evaluate the effect of triethanolamine concentration on the physical stability of formulated pandan leaf lotion, and to determine the triethanolamine concentration that is most stable and effective. Method: Fragrant pandan leaves were extracted with ethanol through maceration. The lotion preparation consisted of 4 formulations with different concentrations of triethanolamine (0%, 2.5%, 3%, and 3.5%). Physical stability was evaluated through organoleptic tests, homogeneity, pH, viscosity, spreadability, adhesiveness, and type of emulsion under room temperature, cooling, and storage conditions for 6 cycles. The data were analyzed using ANOVA, if the data were not normal, the Kruskal–Wallis test was used. Results: The preparation of lotion from the extract of fragrant pandan leaves (Pandanus amaryllifolius Roxb.) in formula 0, formula I, formula II, and formula III has physical characteristics and stability that comply with SNI standards Conclusion: The lotion preparation with 3.5% triethanolamine concentration shows the most stable lotion properties compared to formulation 0, I, and formula II.